THE LIBERAL ISLAMIC THOUGHT IN INDONESIA: SOCIAL CONTEXT AND IMPLICATIONS - Al-MasduQi, Himayatu Syarafatil Furqon; Ghaffari, Fathul (Mozaic: Islamic Studies Journal, 2023)
Social changes in Indonesian society in the modern era cannot be avoided, because society itself has the potential to develop and change. So it becomes a problem for Islam to maintain its existence as a relevant religion at all times. As a manifestation of Islam's response to aligning its teachings with social changes that occurred was the emergence of the liberal Islamic network. Which offers a free mindset and development for individuals. The social situation in Indonesia is also partly influenced by the existence of this network, so it is necessary to study Indonesian social and liberal Islamic networks to find out how the liberal Islamic network influences social conditions in Indonesia. This paper uses library research methods, namely by collecting data such as books, journal articles and literary sources on the topic of social change and liberal Islamic networks.